FUNDAMENTAL CATEGORIES OF COMPETITIVENESS: DEVELOPMENT AND INTERCONNECTION - Гаврікова, Аліна; Самодрига, Яна (SWorldJournal, 2024)
The article reveals the reasons for the consequences of inflationary processes in wartime. The dynamics and assessment of the consumer price index in Ukraine for 2013-2023 are presented. An assessment of the NBU’s actions regarding the implementation of m